Prevalence and Predictors of Stunting among Primary School Children in Northeast Ethiopia - Getaw Walle Bazie; Mohammed Seid; Gudina Egata (Journal of Nutrition and Metabolism)
Background. Stunting is a major public health problem affecting children in low- and middle-income countries and has become one of the underlying causes of early childhood mortality. However, there is a paucity of information on the prevalence of stunting and its predictors among school children in these settings including Ethiopia. Objective. The aim of this study was to assess the prevalence of stunting and its predictors among school children in Northeast Ethiopia. Methods. A school-based cross-sectional study design was used among 341 primary school children in Northeast Ethiopia from October to December 2019. A simple random sampling technique was used to recruit the study subjects. A pretested structured questionnaire was used to collect sociodemographic and dietary data. Anthropometric data were generated using WHO AnthroPlus software version 1.0.4. Binary logistic regression analysis was used to see the association between independent variables and the outcome variable. Odds ratio along with 95% confidence interval was estimated to measure the strength of the association. The level of statistical significance was declared at p value ≤ 0.05. Results. The prevalence of stunting was found to be 14.1% (95% CI: 10.1%, 18.1%). Family size of 6–9 (AOR = 2.43; 95% CI: (1.16, 4.58)), washing hands less frequently before eating (AOR = 3.96; 95% CI: (2.09, 11.66)), and intestinal parasitic infection (AOR = 2.66; 95% CI: (1.16, 4.95)) were significantly associated with stunting. Conclusion. The prevalence of stunting among school-age children was a great public health concern. Large family size, poor handwashing practice before meals, and intestinal parasitosis were significant predictors of stunting. Thus, periodic deworming, health education on personal hygiene, and health promotion and counseling on family planning need to be strengthened by all relevant stakeholders.